Effects of Surface Roughness on the Adhesion and Corrosion Properties of Organic Coating Applied on One Surface of One Sample Set of Mild Steel - Ahmad Helmi Mohd Amin, Ahmad Helmi (Universiti Teknologi Petronas, 2010)
This report basically discusses the research done and basic understanding of the chosen topic, which is the Effects of Surface Roughness on the Adhesion and Corrosion Properties of Organic Coating Applied on One Surface of One Sample Set of Mild Steel. One of the effected areas after performing surface preparation on any metal surface is the surface roughness. The samples for this study are mild steel. Three samples with different surface roughness were prepared. ASTM B 117-90 Salt Spray (Fog) test is carried out in order to study the corrosion behavior and performance in accelerated environment. The adhesion behavior was determined by performing scratch test on the coated surface after underwent the accelerated corrosive environment while the corrosion performance was determined by visual inspection. In this study, oil modified alkyd-based enamel coating is selected as the test sample.